Thermal performance and visualization of the boiling-driven heat spreader - Doh, Su Yoon; Lim, Hyunmuk; You, Seung M.; Lee, Jungho (THERMINIC 2024 - Proceedings of 2024 30th International Workshop on Thermal Investigations of ICs and Systems, 2024)
A boiling-driven heat spreader (BDHS) made of copper was developed and tested for thermal management in high heat flux electronic devices. BDHS features a microporous coating on the heating surface and leverages the bubble-pumping effect to enhance heat dissipation, achieving heat fluxes up to 300 W/cm2 without internal wick structures. This design simplifies fabrication and ensures direction-independent operation. Thermal performance tests confirmed minimal deviation in thermal resistance based on orientation and the absence of dryout even at maximum heat flux. Flow visualization demonstrated that gravity and bubble-pumping influence fluid circulation in the vertical direction, emphasizing the importance of internal channel design. In contrast, horizontal fluid circulation relies mainly on the bubble pumping effect, with less impact from internal design. These findings highlight the promising attributes of BDHS as an effective thermal management solution for high-performance electronic devices, offering improved heat dissipation and operational efficiency in high heat flux applications.
Keywords: Boiling-driven; Bubble pumping; Electronics cooling; Electronics devices; Heat spreaders; Heat spreading; High heat flux; Thermal; Thermal Performance; Wickless; boiling-driven; electronics cooling; heat spreading; visualization; wickless